Health Belief Model Theory Approach to Analyze Pregnant Women's Ability to Prevent Anemia - Irawati, Deasy; Madinah, Ali; Wayanti, Sri; Esyuananik, Esyuananik (Jurnal Kesehatan, 2024)
One of the nutritional problems that often occurs in pregnant women is anemia. The inability of pregnant women to prevent anemia needs to be predicted based on various factors using the Health Belief Model theory. The research aims to analyze the mother's ability to prevent pregnancy anemia using the theoretical approach of the Health Belief Model. The quantitative research method, with a cross-sectional approach, was carried out at the Arosbaya Bangkalan Community Health Center from May to August 2023. The sampling technique was determined using simple random sampling with a sample size of 101 respondents. Data analysis used the Chi-Square Test. Statistical test results perceived susceptibility (ρ=0.000), perceived severity (ρ=0.007), perceived benefits (ρ=0.000), perceived barrier (ρ=1.000) and self-efficacy (ρ=0.028). The research conclusion is that perceived susceptibility, perceived severity, perceived benefits, and self-efficacy influence the ability of pregnant women to prevent anemia. In contrast, perceived barriers do not affect the ability of pregnant women to prevent anemia.